Design and synthesis of CeO2 nanowire/MnO2 nanosheet heterogeneous structure for enhanced catalytic properties. (June 2017) - Du, Haiwei; Wang, Yuan; Arandiyan, Hamidreza; Younis, Adnan; Scott, Jason; Qu, Bo; Wan, Tao; Lin, Xi; Chen, Jianchao; Chu, Dewei
Graphical abstract: Highlights: A CeO2 nanowire/MnO2 nanosheet heterogeneous structure was designed and prepared. The catalytic activity of CeO2 was enhanced by designed core-shell structure. Crystalline MnO2 shell showed better performance than amorphous one. The synergistic effect between CeO2 and MnO2 leaded to enhanced CO oxidation activity. Catalytic properties can be further improved by core-shell compositional optimization. Abstract: A novel CeO2 nanowires/MnO2 nanosheets heterogeneous structure was successfully synthesized by a facile hydrothermal method and its carbon monoxide (CO) catalytic properties were studied. Amorphous MnO2 nanosheets were firstly formed on the surface of CeO2 nanowires to establish a core-shell structure mediated by interfacial redox process which was further transformed to δ-MnO2 through post heat treatment. Compared with as-prepared CeO2 nanowires, CeO2 nanowires/MnO2 nanosheets heterogeneous architecture showed improved catalytic performance because of the strong synergistic interaction between CeO2 and MnO2 at the interface. Moreover, the formation of δ-MnO2 further enhanced the catalytic properties by achieving more defective structures through a slight Mn doping. The catalytic activities can be further enhanced by core-shell compositional optimization. Thus, designing heterogeneous junction was an attractive approach for improving the catalytic properties of CeO2 based nanomaterials.